Shattered [compact disc, unabridged] : a Michael Bennett thriller - Patterson, James, 1947-; Born, James O. (Patterson, James, 1947- Detective Michael Bennett thriller, 2022)
NYPD master homicide investigator Michael Bennett and top FBI abduction specialist Emily Parker have a history. When Emily is found strangled in Washington, DC, only Bennett knows her well enough to find the perpetrator, or so he thinks. At every turn, Bennett discovers that she was a woman as adept at keeping secrets as she was at forging powerful connections. And that those closest to her had both the means and the motives to permanently silence her. Bennett aches to return home to his new wife and the familiar chaos of his family. Yet he's driven to perform the most brilliant detective work of his career, even as the dangerous shadows in Emily's past are closing in around him.